Healthy Living in Hard Times - Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2003)
Using microdata for adults from the 1987-2000 years of the Behavioral Risk Factor Surveillance System, I show that smoking and height-adjusted weight decline during temporary economic downturns while leisure-time physical activity rises. The drop in tobacco use occurs disproportionately among heavy smokers, the fall in body weight among the severely obese, and the increase in exercise among those who were completely inactive. Declining work hours may provide one reason why behaviors become healthier when the economy weakens, possibly by increasing the non-market time available for lifestyle investments. Conversely, there is little evidence that reductions in income play an important role. The overall conclusion is that changes in behaviors supply one mechanism for the procyclical variation in mortality and morbidity observed in recent research.
Keywords: J2; I12; E32; 330; macroeconomic conditions; health; lifestyle behaviors; Gesundheit; Lifestyle; Gesundheitsvorsorge; Konjunktur; Schäzung; Vereinigte Staaten